If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4x = 12 + 6x Solving 3 + 4x = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + 4x + -6x = 12 + 6x + -6x Combine like terms: 4x + -6x = -2x 3 + -2x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -2x = 12 + 0 3 + -2x = 12 Add '-3' to each side of the equation. 3 + -3 + -2x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 12 + -3 -2x = 12 + -3 Combine like terms: 12 + -3 = 9 -2x = 9 Divide each side by '-2'. x = -4.5 Simplifying x = -4.5
| 17-(4m+4)=2+2m-19 | | -7x^6-14x^5+245x^4= | | 36x^2+2.44948974278x-1=0 | | 5x-2=3x-14 | | 10y+1=3(-2y-5) | | 3(z-21)=39-3(z-2) | | 36x^2+2.44948974278-1=0 | | 7w=4w+24 | | 120-3x=15x+18 | | 12f-4=7+f | | a^2-6af-27f^2= | | 7y^3+14y^2=0 | | 3x+1=-x+21 | | 8(3.5)=r | | x^2+25x+35=0 | | 3x+4+2=x-11 | | -13a=h | | 6x^2-54x+24=0 | | -3(14+6)-(-10-4x)= | | 16n=2+15n | | 2x+5=38 | | 5a^2-6a-32=0 | | -3b=42 | | w^2+3w-28= | | 1039-750=c | | 14.2t-25.2=3.8y+26.8 | | 2-3(x+2)=5x-12 | | 1/5(5p+10)=3p-4 | | 3p=36 | | 57-18=t | | 7x-19=4x+2 | | 9.2-4.5=l |